The size of a random surface - Heermann, Dieter W. (International journal of modern physics. C, Computational physics and physical computation, 1991)
The size of a random surface can be measured in at least two ways from two lengths: the radius of gyration and the smallest length such that a box constructed with this length contains the surface. In this paper it is shown that both lengths are non-self-averaging.